Political polarization in Greece. Thematic variations and rhetorical strategies in party manifestos (2012–2019) - Pieridis, Costis; Kountouri, Fani (The Greek Review of Social Research, 2026)
This article examines political polarization in the official party manifestos of Greece’s parliamentary parties during the 2012, 2015, and 2019 national elections. By integrating theoretical perspectives on polarization with a systematic analysis of pre-electoral programs—drawing on data from the Comparative Manifesto Project, the Chapel Hill Expert Survey, and an original typology of “polarizing references”—it explores how thematic priorities, ideological distinctions, and rhetorical strategies shape the political narrative.The study concludes that polarisation in political discourse is not only a reflection of social divisions, but also a tool of political strategy, which is strongly influenced by the ideological identity and the position of each party in the political competition.